2001
DOI: 10.1097/00002820-200108000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Home Caregivers of the Person With Advanced Cancer

Abstract: Australian palliative care services are predominantly community based, with an emphasis on enabling the person to live at home for as long as possible. Home care of the person with advanced cancer receiving palliative care in the community depends largely on the availability of a family caregiver. Family caregivers are required to assess, monitor, and deliver complex therapeutic interventions such as pain and symptom control, including the administration and adjustment of complex medication regimens. This arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
109
1
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(122 citation statements)
references
References 15 publications
5
109
1
7
Order By: Relevance
“…Family members who witness the patient's distress may experience psychological anguish and guilt if they are unable to comfort the patient or obtain the necessary medical assistance to relieve the patient's suffering (3). As well, the burden of caring may adversely affect family members who lack adequate resources or are poorly prepared for the caregiving role (16)(17)(18).…”
Section: Health Of the Family Membersmentioning
confidence: 99%
“…Family members who witness the patient's distress may experience psychological anguish and guilt if they are unable to comfort the patient or obtain the necessary medical assistance to relieve the patient's suffering (3). As well, the burden of caring may adversely affect family members who lack adequate resources or are poorly prepared for the caregiving role (16)(17)(18).…”
Section: Health Of the Family Membersmentioning
confidence: 99%
“…The caregiving burden of terminally ill patients' FCs has been well studied, 12,14,17,[21][22] but few studies have used a longitudinal design to examine changes in caregiving burden. Terminally ill patients' physical condition deteriorates quickly.…”
mentioning
confidence: 99%
“…Therefore, the health and well-being of cancer caregivers have attracted accelerating interest in recent years, and have been studied well in Western countries. [4][5][6][7] Quality of life (QOL) is a term used widely to indicate an individual's general well-being, and has been applied in the field of caregiving for years. Studies conducted in Western countries have *Correspondence: Lie Wang, PhD, Department of Social Medicine, School of Public Health, China Medical University, No.…”
mentioning
confidence: 99%
“…3 Therefore, the health and well-being of cancer caregivers have attracted accelerating interest in recent years, and have been studied well in Western countries. [4][5][6][7] Quality of life (QOL) is a term used widely to indicate an individual's general well-being, and has been applied in the field of caregiving for years. Studies conducted in Western countries have reported that factors associated with caregiver's QOL during the cancer caregiving period could be divided into four categories: (i) sociodemographic characteristics; (ii) caregiving demands; (iii) available psychological and social resources; and (iv) caregiving situation.…”
mentioning
confidence: 99%